2021
DOI: 10.1111/jonm.13467
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the second victim's experience and support on the career success of psychiatric nurses: The mediating effect of psychological resilience

Abstract: Aims We explored the mediating role of psychological resilience in the experience and support of psychiatric nurses as the second victims and their career success. Background Psychiatric nurses, as the primary victims of workplace violence, experience physical and psychological distress, which leads to high resignation rate and job burnout. However, not much is known about the mediating role of psychological resilience between the second victims of workplace violence and their career success. Methods A cross‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Nurses’ career success refers to the unity of positive subjective feelings and objective outcomes of clinical nurses in their career ( Heslin, 2005 ). Studies have shown that career success, as a key protective factor for nurses’ career development, has positive effects in reducing nursing brain drain and ensuring the quality of nursing service ( Sönmez et al, 2021 ; Xu et al, 2021 ). The results of this study show that the median total score of career success of female nurses in central China is 68, which is in the medium level, lower than the results of Dan’s study on career success of nurses in mainland China, indicating that there is still some room for improvement ( Dan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses’ career success refers to the unity of positive subjective feelings and objective outcomes of clinical nurses in their career ( Heslin, 2005 ). Studies have shown that career success, as a key protective factor for nurses’ career development, has positive effects in reducing nursing brain drain and ensuring the quality of nursing service ( Sönmez et al, 2021 ; Xu et al, 2021 ). The results of this study show that the median total score of career success of female nurses in central China is 68, which is in the medium level, lower than the results of Dan’s study on career success of nurses in mainland China, indicating that there is still some room for improvement ( Dan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the mediating effect analysis showed that craftsmanship partially mediated the relationship between psychological resilience and career success among female nurses in central China, with the mediating effect value of craftsmanship being 0.138, accounting for 39.3% of the total effect, indicating that nurses’ career success can be predicted not only by psychological resilience directly, but also by this mediating variable of craftsmanship level. Nurses with higher psychological resilience have better work stability and motivation, and are not only better able to adapt to their work, but also more able to actively regulate their own state and rationally seek solutions when facing difficulties and pressures at work, so as to achieve better work results and career success ( Xu et al, 2021 ); and for individual nurses, a better craftsmanship enables them to seek higher professional values in the work process, exercise and develop their personal abilities while completing their work, and thus achieve their professional goals and values ( Jang et al, 2016 ). Thus, it shows that the craftsmanship, psychological resilience and career success of female nurses play a positive role, and craftsmanship has a significant mediating effect between psychological resilience and career success.…”
Section: Discussionmentioning
confidence: 99%
“…However, research on nurses' career success remains in its infancy (Xu et al, 2022). Therefore, promoting nurses' career success, increasing their sense of achievement and reducing their turnover rate are crucial to solve nursing shortage problems.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses' career success is accompanied by strong work motivation, secured well‐being and low turnover intention (Liu & Liu, 2016; Liu et al, 2015; Spurk, Hirschi, et al, 2019). However, research on nurses' career success remains in its infancy (Xu et al, 2022). Therefore, promoting nurses' career success, increasing their sense of achievement and reducing their turnover rate are crucial to solve nursing shortage problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation